The Veterinary Microbal Germ Plasm Applicability on Animal Husbandry Development: The Future Expectation of Enterotoxigenic, Enteropathogenic and Verotoxigenic Locally Isolated Escherichia Coli Vaccines for Controlling Neonatal Colibacillosis in Piglets and Calves - Supar . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2001)
Enterotoxigenic Escherichia coli (ETEC) strains are the major causes of neonatal diarrhoea in piglets and calves. The prevalence of diarrhoeal cases and mortality in neonatal piglets were reported to occur between 13 to 44% and 12 to 32% respectively. Similar problems were observed in neonatal dairy calves, at which the diarrhoeal cases and mortality were reported at an average of 20 to 30% and 24% respectively. ETEC containing either K88, K99, F41 or 987P fimbrial antigen isolates were commonly associated with piglet diarrhoea, whereas ETEC bearing K99, F41 or K99F41 fimbrial antigens associated with calf diarrhoea. Both of the ETEC isolates were known to exhibit multiple resistance between 4 to 6 antibiotic drugs, or even up to 9 to 15 antibiotic drugs commonly used in the field. These indicated that antibiotics were no longer effective to be used to treat and to control piglet and calf diarrhoea associated with ETEC. Inactivated multivalent ETEC vaccine containing K88, K99, F41 and 987P antigens was developed from local isolates and adjuvanted with alumium hydroxide gel at final concentration of 1,5% and cell concentration was equal to the number 10 of the McFarland tubes standard. Two doses of 2 ml vaccine were subcutaneously injected into pregnant sows at 6 weeks and 2 weeks before expected date of forrowing. New born piglets were allowed to suckle their own mother under field conditions. Similar vaccine was prepared from ETEC K99, F41, K99F41 and verotoksigenik E. coli (VTEC) field isolates originated from calves with diarrhoea as described above. Two doses of  5 ml ETEC vaccine were injected subcutaneously of pregnant dairy cows of 6 weeks and 2 weeks before expected date of calving. Calf born from vaccinated cow was given colostrum of its owm mother by the milk man. A killed whole cell multivalent ETEC vaccine containing K88, K99, F41 dan 987P injected intramuscularly or subcutaneously into pregnant sows induced antifimbrial IgG and IgA responses both in serum which was predominated by IgG, and in the mammary secretions were both IgA and IgG. In other words such vaccines provided passive protection to piglets which be able to suckle colostrum at birth. Similar antibody responses were demonstrated in dairy cows vaccinated with ETEC containing K99, F41 fimbrial antigens and E. coli producing verotoxin antigen (VTEC). Vaccine field trials to control piglet neonatal colibacillosis in swine that two doses of multivalent vaccine given four weeks apart  in pregnant sows at late gestation provided dramatically reduced piglet diarrhoea and mortality from 30% (unvaccinated) to 5% (vaccinated). The use of 2 doses of ETEC K99, F41 and VTEC in pregnant dairy cows at late gestation reduced the calf diarrhoea and mortality from 13.0% annualy (before vaccine application) to 0.7% (vaccine application period). The two types of vaccine (multivalent ETEC for pigs and ETEC+VTEC for cattle) demonstrated a good prospect, since these whole cell vaccines  are highly efficacious in controling neonatal piglet and calf diarrhoea and mortality. These vaccines could be used to replace antibiotic therapy in the future. The  ETEC, EPEC and VTEC local isolates are preseved at the Balitvet culture colection (BCC) Bogor.   Key words: Piglets, calves, microbial germ plasm, ETEC, EPEC, VTEC, colibacillosis, vaccines, field control